Effect of posterior gingival smile on the perception of smile esthetics - Rodríguez-Martínez, Alicia (Medicina Oral S.L., 2014)
Objectives: To evaluate and compare the influence of posterior gummy smile on the perception of smile esthetics by orthodontists, general-dentists and laypersons. Study Design: A frontal photograph of a smile with normal gum exposure was chosen and manipulated digitally using Adobe Photoshop C3 to generate three further images with posterior gum exposure of 4, 6 and 8mm. These four images were assessed by the three evaluator groups: orthodontists (n=40), general-dentists (n=40) and laypersons (n=40). Both orthodontists and dentists had at least ten years professional experience and laypersons were aged between 40-50 years. The proportion of men to women was 20:20 in each group. Evaluators awarded a score to the smile esthetics of each image: 1=acceptable, 2=moderately acceptable, 3=unacceptable. Afterwards, each evaluator placed the four images in order of esthetic preference. Results: No significant differences (p>0.05) were detected between the three evaluator groups for the photo without posterior gummy smile. The perception of smile esthetics for a the 4mm posterior gummy smile (median for orthodontists=2, general-dentists= 1, laypersons=1), the 6mm (median for orthodontists=2, general-dentists=1, laypersons=1) and the 8mm (median for orthodontists=3, general-dentists=2, laypersons=2) was significantly different between orthodontists and the other two evaluator groups (p<0.0017). The three evaluator groups coincided in placing the image with the 6mm gum exposure in first place in order of esthetic preference. Conclusions: Posterior gummy smile influences the perception of smile esthetics more negatively among orthodontists than the rest of the groups. Key words:Aesthetics, gummy smile back, orthodontists, dentists, laypersons.